Effects of long-term rainfall decline on the structure and functioning of Hawaiian forests. (22nd August 2017) - Barbosa, Jomar M; Asner, Gregory P
Abstract: Climate change is altering the dynamics of terrestrial vegetation, with consequences for the functioning of Earth's biomes and the provisioning of ecosystem services. Changes in forest dynamics due to drought events or short-term drying trends have been described at different ecological scales, but few observational studies have determined the relative effects of short- and long-term precipitation trends (e.g. decade and century, respectively) on forest canopy structure and functioning. Using gridded annual precipitation maps from 1920 to 2012, and temporal data from airborne light detection and ranging (LiDAR) and MODIS Enhanced Vegetation Index (EVI), we present evidence for a large-scale decline in forest canopy volume (area vs. height) and greenness (a metric of photosynthetic function) driven by a long-term drying trend on Hawaii island. Decreases in canopy greenness were observed in step with shorter-term (10 y) precipitation declines, but decreases in greenness were two-fold greater where longer-term (∼100 y) precipitation declines had occurred. Canopy volume mainly reduced where long-term precipitation declines occurred. We conclude that long-term precipitation trends critically impact forest canopy structure and functioning, which likely has cascading consequences for numerous ecological processes such as subcanopy light availability, species interactions, carbon storage, and animal habitat.